Determinants on the volume of the peer-to-peer (P2P) lending platforms in China - JIAO, NI (2018)
The Peer-to-Peer lending (P2P lending) is an innovative financial product of private lending with the applications of the Internet. Currently, many banks have already cooperated with the P2P lending platforms or even add this service into their lending with the purpose of making more profit. This experiment is a deep investigation into the determinants on the volume of the P2P lending platform in China. In our empirical study, we collect the data from the WDZJ database (the largest P2P lending database in China), remove all the problematic platforms, select 13 related variables, and take 84 platforms from 16 provinces as a sample. Although the sample size is not very big due to the restrictions of the website, it still helps to figure out which kind of factor dominantly affects the volume of the P2P lending and the relationship among those variables. Through establishing the Fixed effect model, we found that the borrowing rate and the risk factors are negatively associated with the volume of P2P lending, while the social capital, two macroeconomic indexes (the inflation rate and the CPI index) and three categorical variables (the local economy, the location of the platform, the type of platform) have the positive impact on its performance. Some suggestions on how to improve the performance of the P2P lending platform are given in the conclusion from the perspective of the government, the platform itself and the commercial banks. Keywords: the P2P lending, the volume of the P2P lending, determinants